INCREASING COMPETENCE INNOVATIONS MANAGEMENT BY IMPROVING THE PROCESS OF THEIR PREPARATION - A. Fayustov (Publishing House of the State University of Management, 2016)
This article discusses methods for training managers in the field of innovation management from the point of view of the formation of their professional competence by means of the educational process. The examples and the results are some of the different types of training on specific subjects in the educational process of preparation of bachelors direction «Innovation» at the State University of Management (including and using the online form).